2010
DOI: 10.1086/652803
|View full text |Cite
|
Sign up to set email alerts
|

How Stable Is the Hepatitis C Virus (HCV)? Environmental Stability of HCV and Its Susceptibility to Chemical Biocides

Abstract: This study assessed the environmental stability and susceptibility to chemical biocides of HCV. The results should be useful in defining rigorous disinfection protocols to prevent nosocomial transmission of HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
0
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 35 publications
8
50
0
10
Order By: Relevance
“…Importantly, fusion in all these systems depends on a transient acidification, consistent with HCV entry dependence on endosomal acidification [146,147]. Yet, HCVcc are pH resistant [78,178], indicating that a first trigger may be needed to render the glycoprotein fusogenic. Consistent with this, cell-to-cell and cell-surface fusion assays depend on a 37°C incubation period with the target cells prior to the acidic treatment.…”
Section: Endocytosis and Fusion Of Hcvmentioning
confidence: 66%
See 1 more Smart Citation
“…Importantly, fusion in all these systems depends on a transient acidification, consistent with HCV entry dependence on endosomal acidification [146,147]. Yet, HCVcc are pH resistant [78,178], indicating that a first trigger may be needed to render the glycoprotein fusogenic. Consistent with this, cell-to-cell and cell-surface fusion assays depend on a 37°C incubation period with the target cells prior to the acidic treatment.…”
Section: Endocytosis and Fusion Of Hcvmentioning
confidence: 66%
“…Data on HCVcc storage are sparser. Briefly, we found that HCVcc (Jc1 or Luc-Jc1 virus) has a half-life of 6 hours at 37°C, 3.5 days at room temperature and 11 days at 4°C [178]. Other teams reported JFH-1 virus stability at 4°C for up to 4 or 6 weeks [6,190], a difference that might be imputable to the different virus strains and titers.…”
Section: Preparation Concentration and Storage Of Hcvccmentioning
confidence: 84%
“…Whereas HCV contained in culture supernatant retains full infectivity when stored for 1 week at 4°C, for example (70), infectivity of captured virus samples is reduced by up to 100-fold within 16 h at 4°C. Therefore, analyses of infectious virions after capture by using density gradient centrifugation were difficult as infectivity was FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
“…2). Furthermore, poor stability of virions makes the purification process extremely time-sensitive, limiting the number of purification steps that can be undertaken before most of the infectivity is lost (11). Finally, propensity to forming aggregates has been observed, preventing tandem affinity purification approaches (Fig.…”
Section: Discussionmentioning
confidence: 99%